The Tourist Behaviour of Finnish Students: A Case Study from the University of Joensuu - Płachta, Marta (Turyzm/Tourism, 2004)
The article presents the typical tourist behaviour of the present generation of Finnish students. It considers the spatial differentiation of student holiday destinations and describes characteristic forms of holiday.